English Teachers' Perception of Implementing Project-Based Learning in Secondary Schools - Sartika, Utari Dwi; Syafryadin, Syafryadin; Azwandi, Azwandi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
The aims of this study were to investigate English teachers’ perceptions in implementing Project-Based Learning and to analyze the English teachers’ challenges of implementing Project-Based Learning in Secondary Schools in Bengkulu City. 16 English teachers in Senior High Schools and 14 English teachers in Junior High Schools who have implemented Project-Based Learning in their class served as participants in this study. An explanatory sequential mixed method research applied to investigate the teachers’ perceptions in implementing Project-Based Learning for gathering quantitative data by using Questionnaire in the first phase. Then, in collecting qualitative data to analyze the challenges of the implementation of Project-Based Learning in English classroom, the researcher conducted interview which explained the result in the first phase. There are a total of 30 questions on the questionnaire, all of which pertain the internal factors and the external factors, also the challenges which affected the English teachers’ perceptions in Secondary School. The findings of this study suggested English teachers’ perceptions and challenges in implementing Project-Based Learning in Secondary Schools had a positive response. Meanwhile, the English teachers’ challenges are caused by the limited of time and of  knowledge, the management of class, and the situation of pandemic.